2000
DOI: 10.1038/sj.onc.1203636
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of c-myc apoptotic pathways

Abstract: All biological functions mediated by the c-myc oncoprotein require an intact transactivation domain (TAD). We compared TAD mutants for their ability to promote apoptosis of 32D myeloid cells in response to interleukin-3 (IL-3) deprivation and exposure to chemotherapeutic drugs, and to activate ornithine decarboxylase, an endogenous c-myc target. Di erent sub-regions of the TAD were required to mediate each function. cDNA microarrays were then used to identify multiple c-mycregulated transcripts, some of which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 59 publications
6
79
0
Order By: Relevance
“…Growth kinetics in limiting interleukin-3 (IL-3) concentrations (50 pg ml À1 ) were monitored as in (c). (e) Rat1a-GpIba and Rat1a-vector cells were grown to approximately 50% confluency and then deprived of serum (Nesbit et al, 2000). At the times indicated, viable cell counts were determined in triplicate.…”
Section: Gpiba Promotes Growth and Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…Growth kinetics in limiting interleukin-3 (IL-3) concentrations (50 pg ml À1 ) were monitored as in (c). (e) Rat1a-GpIba and Rat1a-vector cells were grown to approximately 50% confluency and then deprived of serum (Nesbit et al, 2000). At the times indicated, viable cell counts were determined in triplicate.…”
Section: Gpiba Promotes Growth and Survivalmentioning
confidence: 99%
“…Isolation of RNA was performed as described (Nesbit et al, 2000). Preparation of biotinylated RNA (cRNA) was performed by the PittArray DNA Microarray Facility of the Genomics and Proteomics Core Laboratories at the University of Pittsburgh Medical Center.…”
Section: Dna Microarraysmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that an expressed sequence tag (#697416, Nesbit et al, 2000) is markedly downregulated in 32D cells constitutively expressing high levels of c-Myc. The complete sequence of this EST, obtained in our laboratory, is 100% homologous to the reported sequence of 'onzin', which was independently sequenced and deposited in GenBank (Accession No.…”
Section: Onzin Is Highly Conserved and Its Expression Is Tissue-restrmentioning
confidence: 99%
“…As an alternative for characterizing c-Myc targets, we have utilized the murine 32D myeloid cell line and identified >80 putative c-Myc target genes by transcriptional profiling (Nesbit et al, 2000). Among those so far evaluated are MT-MC1 and CCL6 Yi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%